2019
DOI: 10.1093/nar/gkz562
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of scaffold/matrix attachment regions in human genome: a data mining exercise

Abstract: Scaffold/matrix attachment regions (S/MARs) are DNA elements that serve to compartmentalize the chromatin into structural and functional domains. These elements are involved in control of gene expression which governs the phenotype and also plays role in disease biology. Therefore, genome-wide understanding of these elements holds great therapeutic promise. Several attempts have been made toward identification of S/MARs in genomes of various organisms including human. However, a comprehensive genome-wide map o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 81 publications
7
37
0
Order By: Relevance
“…Because of their AT richness, it was initially proposed that S/MARs were present densely within dark G bands [30]. Mapping of human S/MARs using ChIP‐seq data of 14 S/MAR binding proteins was recently achieved [31]. These sites were confirmed to contain the previously described features including AT richness.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Because of their AT richness, it was initially proposed that S/MARs were present densely within dark G bands [30]. Mapping of human S/MARs using ChIP‐seq data of 14 S/MAR binding proteins was recently achieved [31]. These sites were confirmed to contain the previously described features including AT richness.…”
Section: Resultsmentioning
confidence: 80%
“…(G–I) Abundance of H1 variants at retroviral integration sites and S/MAR protein binding sites. Average, input‐subtracted ChIP‐seq signal of H1.2 and H1X around the center of S/MARs sites (mapped in [31]) (G), HIV‐1 integration sites (H), or around the center of the S/MAR binding protein sites indicated (I).…”
Section: Resultsmentioning
confidence: 99%
“…These two arginines protrude into the characteristically narrow minor groove of the A-tract. A-tract regions, which are abundantly present in S/MAR (scaffold/matrix attachment regions) (58) and satellite sequences (26), are known to have the narrowest minor groove, and hence have a high density of negative charges. Moreover, A-tracts complementary to deoxy-uracils would have very similar minor groove widths to A-tracts complementary to thymines.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix attachment regions (MARs) are cis-acting DNA elements and known to act as epigenetic regulatory sequences that increase gene expression [95]. Ley et al [96] demonstrated that incorporation of human MAR 1-68 in a PB transposon cassette was beneficial for reduced silencing effects and caused increased transgene expression in cultured cells.…”
Section: Use Of Epigenetic Regulatory Elementmentioning
confidence: 99%